IDENTIFIKASI KARAKTER KEWIRAUSAHAAN MAHASISWA STKIP PGRI SIDOARJO - Tri Achmad Budi Susilo (LPPM STKIP PGRI Sidoarjo, 2020)
STKIP PGRI Sidoarjo is an educational institution and teaching staff in which curriculum design is designed to print students into educators. Entrepreneurship courses at STKIP PGRI Sidoarjo are subjects that must be taken by students with learning outcomes so that students gain knowledge and skills in running entrepreneurship. The purpose of this study was to identify the entrepreneurship character of PGSD study program students and Historical education study program STKIP PGRI Sidoarjo. This type of research is quantitative while the instrument used is a questionnaire test. The population used is PGSD study program students and History education who are currently attending entrepreneurship courses. The sample used was 56 students. The results showed 22 or 39.3% of students had a high entrepreneurial character, 28 or 50% of students had a moderate entrepreneurial character and 6 or 10.7% of students had a low entrepreneurial character. This shows that, even though students study at educational institutions and teaching staff, the professional teacher printing institute turns out to have a high interest in becoming an entrepreneur.